Assessing the dry matter intake and enteric methane emissions of pre-partum dairy cows offered grass clover or grass-only silage from two different silage systems - Kennedy, Michael; Lahart, Ben; Herron, Jonathan; Boland, Tommy M.; Fleming, Christina; Egan, Michael (Frontiers in Animal Science, 2024)
Over the winter period low grass growth and availability in pasture based dairy systems results in animals being housed and predominantly fed a diet of grass silage. There is limited availability of methane (CH4) data evaluating the impact of forage type in dairy cows over the pre-partum period. The objective of the current experiment was to evaluate feeding grass clover (GC) silage and grass only (GO) silage on dry matter intake (DMI) and enteric CH¬4 emissions in dairy cows pre-partum. A complete randomised block design was conducted for the six-week experiment over two winter periods; December 2020 to January 2021 and December 2021 to January 2022. In each year, 30 non-lactating pregnant dairy cows were randomly allocated to two treatments (n=15). In both years, cows in the GC treatment were offered grass clover bale silage, while cows in the GO treatment were offered grass only pit silage. Individual animal DMI and gaseous emissions were monitored daily using Hokofarm RIC feed stations and Greenfeed technology. Grass clover silage consistently had greater (P<0.05) organic matter (OM) digestibility and lower (P<0.05) NDF and ADF content when compared to the GO silage. Cows in the GC treatment had significantly greater (P<0.05) total DMI (TDMI) compared to the GO treatment cows. Daily CH4 emissions (g/d) were not affected by treatment; however, cows in the GC treatment had reduced (P<0.05) CH4 yield (g/kg TDMI). Offering dairy cows grass clover silage over the pre-partum period resulted in greater DMI with reduced CH¬¬4 yield, when compared to cows offered grass only silage.